Alive and Kicking — The Story of Lesion and the Civil Code of Québec - Wilson, Kerianne (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 2010)
Québec civil law had excluded lesion between majors entirely from the Civil Code of Lower Canada. The changing social climate of the 1950s and 1960s and the accompanying popularity of the philosophy of contractual justice set the stage for the Civil Code Revision Office and a dramatic reversal of the place of lesion in Québec law. But this expectation came to nothing as lesion between majors was, for all intents and purposes, excluded from the Civil Code of Québec. In recent years, however, the judiciary has used other means, namely abusive clauses and economic error, to reach the same end to a large extent. The result is desirable, but the legitimacy of this initiative remains controversial.